Twin carbons: The carbonization of cellulose or carbonized cellulose coated with a conducting polymer, polyaniline. (November 2016) - Bober, Patrycja; Kovářová, Jana; Pfleger, Jiří; Stejskal, Jaroslav; Trchová, Miroslava; Novák, Ivan; Berek, Dušan
Abstract: The strategies of the preparation of twin carbon materials, a carbon produced by the carbonization of cellulose combined with a nitrogen-containing carbon resulting in similar process from conducting polymer, have been investigated. Cellulose or carbonized cellulose was used as templates for the coating with a conducting polymer, polyaniline, followed by their carbonization. Such approach allows for the preparation of novel nanostructured carbonaceous systems. The process was followed by FTIR and Raman spectroscopies and by thermogravimetric analysis. The conductivity, specific surface areas, and elemental compositions of templates, intermediates, and twin carbons have been determined, and are discussed along with their morphology. Graphical abstract: